Pinched hypersurfaces are compact - Bourni Theodora; Langford Mat; Lynch Stephen (Advanced Nonlinear Studies, 2023)
We make rigorous and old idea of using mean curvature flow to prove a theorem of Richard Hamilton on the compactness of proper hypersurfaces with pinched, bounded curvature.